Application of Taguchi model to valuation of information security technology considering security quality failure. (3rd July 2020) - Jeong, Yujin; Yoon, Byungun
Abstract : As interests in intangible assets in a digital economy have been growing, technology valuation is becoming increasingly more important in information technology management. Most existing valuation methods do not reflect the unique characteristics of technology. Thus, this paper aims to suggest an approach for technology valuation that considers the nature of information security technology. First, technological value is evaluated by scoring value factors that are used to analyse the intrinsic characteristics and application of technology. Second, to evaluate the market value, the expected profit of the technology will be deduced by using an income approach, reflecting on the characteristics of information security products and services. The weighted sum of factors from the previous scoring process plays a role in adjusting the expected profit. Third, the Taguchi loss function is applied to calculate the amount of social loss incurred due to the lower quality level of security. The final result of technology valuation is presented by integrating the expected profit and social loss. The proposed approach is illustrated with a case of safe symmetric key algorithm, one of information security technologies in Korea. The results of technology valuation will provide objective information for technology transfer and the selection of R&D projects.